PENGOLAHAN BAN BEKAS BERWAWASAN LINGKUNGAN MENJADI BAHAN BAMPER PADA OUTOMOTIF - Bukit, Nurdin; Frida, Erna (Teknologi Indonesia, 2011)
On the minimizing of waste tires which can damage the environment can be done by processing waste tires into powder waste tires and used as a fi ller in the manufacture of thermoplastic elastomer composite which can be used as bumpers on automotive. The Research has been done by mixing the powder waste tires, SIR-20 compound and polypropylene,with Polipropilena Maleic anhydride compatibilizer. Preparation of raw materials is done by making rubber compound with two roll mill mixing equipment. Composite made by blending process at temperature of 180C with a speed of 60 rpm in an internal mixer, with composition (30, 40, 50)% weight and size of 1mm and 60 mesh, composite results in a granular form in the molding hot press, cold, then made in to specimens for each test sample in accordance with JIS K 6781 standard size for tensile test. The Results obtained from mechanical test properties waste tires size 60 mesh powder better than the size of 1mm. The best mechanical properties obtained on the composition of 50% with a maximum of 13 MPa tensile strength and elongation at break 148%. The result of SEM analysis of morphology 60 mesh size is more than homogeneous than 1mm.